Collocation of the word "weather" in the city of Bekasi (ecolinguistic study using a corpus linguistics approach on tribunbekasi.com media) - Anam, Ahmad; Purnama, Yogi; Alhamidi, Luban (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This study aims to examine the collocation of the word "weather" to Bekasi City which appears in the bold news media TribunBekasi.com from January 2023 to March 2023 using a corpus linguistics approach. The main goal is to prove the negative issues that some netizens have done regarding the weather in Bekasi City so that they become the object of ridicule by netizens. Based on the data collected, the word "weather" in Bekasi City ranks 15th. As a result, the entry "weather" is the dominant entry in the TribunBekasi.com media news articles. Evidenced by the number of occurrences of 96 times and is ranked 15th. Overall, there are 96 occurrences of the word "weather" from the corpus. From the news articles collected, we can find out the synonyms or collocations of the word "weather". Apart from that, we can also find out the weather conditions in Bekasi City, for example sunny, cloudy, rainy, bad, and light.